Legal Vacuum Analysis and the Need for Criminal Policy Reformulation in Handling Cyberbullying Cases in Indonesia based on the Perspective of Child Protection and the Law on Electronic Information and Transactions - Sekar, Aji Yoga; Setiono, Joko; Sutrisno, Sutrisno (Greenation Publisher & Yayasan Global Resarch National, 2025)
The rapid development of digital technology has created a new space for internet-based crimes, one of which is cyberbullying targeting children as victims. This phenomenon continues to rise in Indonesia, in line with the high rate of social media usage among minors. Nevertheless, the existing legal system has not been sufficiently responsive in addressing cyberbullying specifically, especially when viewed from the perspective of child protection. The Law on Electronic Information and Transactions (Law No. 11 of 2008 in conjunction with Law No. 19 of 2016) does not explicitly regulate cyberbullying as a criminal offense, while the Child Protection Law (Law No. 23 of 2002 in conjunction with Law No. 35 of 2014 and Law No. 17 of 2016) also does not adequately cover digital-based violence. This normative and implementative gap creates difficulties in prosecuting perpetrators and risks neglecting the rights of children who are victims of cyberbullying. This paper analyzes the need for a reformulation of criminal policy through the establishment of specific norms that explicitly criminalize cyberbullying against children. The research uses a normative juridical approach and emphasizes the importance of integrating child protection into every criminal legal policy in the digital era. The proposed reformulation includes revising the norms in the ITE Law and the Child Protection Law, as well as strengthening the roles of law enforcement officers and digital platforms. The findings of this study highlight the urgency of criminal law reform that is not only repressive, but also preventive and rehabilitative for child victims.